Development of a methodological basis for assessing the effectiveness of value-oriented management of development of a restaurant business enterprise - Grosul, Victoria; Balatska, Natalia (Technology audit and production reserves, 2021)
The object of research is the process of value-oriented management of the development of a restaurant business. The article argues that value-oriented management of the development of a restaurant business is aimed at achieving the goal of maximizing the key determinants of value. The parameters and elements of the configuration of the value concept (strategic assets, nomadic competencies, the consumer value frame of the restaurant service) are determined, the content and nature of which reflects the individual elements of the value-oriented management of the restaurant business. The research methodology is based on theoretical and methodological analysis of scientific literature, economic methods, and observations, comparable, measurement, analysis and matrix modeling. To develop a Y-matrix model for assessing the effectiveness of value-based development management, which represents the relationship between strategic assets, key competencies and the value frame, the expert method and the method of multivariate comparative analysis are used. The results of this research show that the elements of consumer value that are basic for the development of restaurant businesses in the modern competitive space are: the uniqueness of the restaurant concept, originality of the menu, pricing policy, service, safety standards, atmosphere, innovation and emotions. For the empirical convergence of the concept of value, a Y-matrix is built. Based on the use of the method of multivariate comparative analysis, the implementation degree of key competencies and strategic assets in the creation of structural elements of consumer value is assessed. To determine the efficiency level of value-based development management at the restaurant business, the value resonance coefficient is calculated. Based on the research results, a list of key competencies is determined, on the development of which it is necessary to focus the attention of the management of the restaurant business. The practical significance of research lies in the possibility of its use as a tool for strategic value analysis in the restaurant business. The proposed approach allows to determine the emphasis of management impact in order to maximize the value of restaurant services.